THE EFFECT OF USING PICTURE SERIES MEDIA ON STUDENTS' WRITING ABILITY IN INDONESIAN LANGUAGE LEARNING IN STATE ELEMENTARY SCHOOLS IN PALEMBANG CITY - Yasir Arafat; Wahid Ibrahim.B.N; Yuni Puji Astuti (Cerdas Proklamator, 2026)
Writing is an essential language skill in Indonesian language learning, especially at the elementary school level. This skill not only requires students to construct sentences but also to develop ideas, imagination, and express thoughts in a coherent and clear manner. However, many students still face difficulties in writing, particularly in arranging simple sentences systematically. Therefore, engaging and effective learning media are needed to help improve students’ writing skills, one of which is serial picture media. This study aims to determine the effect of using serial picture media on the writing skills of second-grade students at SDN 13 Palembang. The research method used was an experimental method with a Pretest-Posttest Control Group Design. The sample consisted of 56 students, divided into 28 students in the experimental class and 28 students in the control class. Data collection techniques were carried out through written tests in the form of pretest and posttest, and analyzed using normality tests, homogeneity tests, and hypothesis testing (t-test) with the assistance of SPSS version 25. The results showed that the average posttest score of the experimental class was 78,75, while the control class was 60,89. The data were homogeneous with a significance value of 0.119 > 0.05. The hypothesis test showed a significance value of less than 0.025, indicating a significant effect. Thus, serial picture media is effective in improving students’ writing skills.